ABOUT PREDATORY PUBLISHING : what it is and how to recognize it? - Azizova, F.L.; Okhunov, A.O.; Khudaibergenova, N.SH. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
This review article is devoted to the concept, history, and methods of recognizing predatory logs. Such journals, as usual, are published in the open-access mode. They are periodical and claim the status of scientific journals. However, at the heart of these types of journals is a key element of an unfair model of scientific publishing, which involves charging authors of manuscripts without providing full editorial or publishing services (including a full peer review system) accepted in real scientific journals (open and limited access). The article describes the history of the study of the issue and methods for identifying such publications in order to increase the vigilance of young scientists.